Gemella asaccharolytica sp nov., isolated from human clinical specimens - ÜLGER, NURVER (MICROBIOLOGY SOC, 2010)
Three strains of an unidentified Gram-stain-variable, fastidious, catalase-negative, capnophilic, non-spore-forming, coccus-shaped bacterium from human wound specimens were characterized by phenotypic and molecular taxonomic methods. Initially, these strains were anaerobic; with repeated culture, they became aerotolerant. Comparative 16S rRNA gene sequencing studies demonstrated that the unknown strains were genealogically homogeneous and constituted a novel subline within the genus Gemella. The unknown bacterium was readily distinguished from other Gemella species by biochemical tests. On the basis of both phylogenetic and phenotypic evidence, it is proposed that the unknown bacterium from clinical specimens be classified as Gemella asaccharolytica sp. nov. The type strain is WAL 1945J(T) (=ATCC BAA-1630(T) =CCUG 57045(T)).
Keywords: ORGANISM; COCCI